2016
DOI: 10.1002/art.39474
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Six‐Week Treatment of Axial Spondyloarthritis Patients With an Optimal Dose of Nonsteroidal Antiinflammatory Drugs: Early Response to Treatment in Signal Intensity on Magnetic Resonance Imaging of the Sacroiliac Joints

Abstract: Objective. To evaluate the early effect of full-dose nonsteroidal antiinflammatory drugs (NSAIDs) on the extent and intensity of bone marrow edema of the sacroiliac (SI) joints on magnetic resonance imaging (MRI) in axial spondyloarthritis (SpA).Methods. A single-center, 6-week study of a cohort of consecutive patients with clinically suspected axial SpA was conducted. A total of 117 patients were screened. Forty patients who were diagnosed as having axial SpA and had presented with a positive MRI of the SI jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 21 publications
2
18
0
1
Order By: Relevance
“…All patients demonstrated a good response to NSAID. Although the dose and duration of NSAID required to alter BME is unclear, our data support previous reports in the literature 2 . We acknowledge that the effect of NSAID cannot be quantitatively measured from these series, particularly as postinflammatory changes were still visible in 2 cases after 5 weeks.…”
Section: Rheumatologysupporting
confidence: 89%
“…All patients demonstrated a good response to NSAID. Although the dose and duration of NSAID required to alter BME is unclear, our data support previous reports in the literature 2 . We acknowledge that the effect of NSAID cannot be quantitatively measured from these series, particularly as postinflammatory changes were still visible in 2 cases after 5 weeks.…”
Section: Rheumatologysupporting
confidence: 89%
“…However, maintaining a high NSAID index is not well tolerated in daily clinical practice . Furthermore, a recent study showed that full‐dose NSAID treatment did not achieve a favorable response or a relevant decrease in sacroiliitis on MRI . Therefore, if a patient showed elevated CRP levels despite conventional NSAID treatment, timely switching to or adding TNFi treatment could be a proper strategy for inflammation control and inhibition of radiographic progression in early AS.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent report by Varkas and colleagues described the results of a study of 6‐week treatment of axial SpA with an optimal dose of NSAIDs . In the 20 patients who completed the study, there was a reduction of 1.1 units (10.5%) in the mean Spondyloarthritis Research Consortium of Canada (SPARCC) MRI score for SI joint inflammation at week 6 versus baseline ( P = 0.032).…”
Section: Discussionmentioning
confidence: 99%